Fructose co-ingestion to increase carbohydrate availability in athletes - Fuchs, C. J.; Gonzalez, L. T.; van Loon, L. J. C. (The Journal of Physiology, 2019)
Carbohydrate availability is important to maximize endurance performance during prolonged bouts of moderate- to high-intensity exercise as well as for acute post-exercise recovery. The primary form of carbohydrates that are typically ingested during and after exercise are glucose (polymers). However, intestinal glucose absorption can be limited by the capacity of the intestinal glucose transport system (SGLT1). Intestinal fructose uptake is not regulated by the same transport system, as it largely depends on GLUT5 as opposed to SGLT1 transporters. Combining the intake of glucose plus fructose can further increase total exogenous carbohydrate availability and, as such, allow higher exogenous carbohydrate oxidation rates. Ingesting a mixture of both glucose and fructose can improve endurance exercise performance compared to equivalent amounts of glucose (polymers) only. Fructose co-ingestion can also accelerate post-exercise (liver) glycogen repletion rates, which may be relevant when rapid (<24 h) recovery is required. Furthermore, fructose co-ingestion can lower gastrointestinal distress when relatively large amounts of carbohydrate (>1.2 g/kg/h) are ingested during post-exercise recovery. In conclusion, combined ingestion of fructose with glucose may be preferred over the ingestion of glucose (polymers) only to help trained athletes maximize endurance performance during prolonged moderate- to high-intensity exercise sessions and accelerate post-exercise (liver) glycogen repletion.